The potential benefits of recycling construction wastes / Aldrinne Cyril - Cyril, Aldrinne (2021)
Recycling is one of the methods which focus on handling construction waste. Promoting the benefits of the recycling method for construction waste can create a positive perception in using recycling for handling construction waste. The number of construction wastes genuinely increase due to the high demand for buildings and infrastructure works for development. Lack of exposure to recycling can affect the regularity and efficiency of recycling practices. Disposing of construction waste to landfill involves large area and cause availability of land to deplete. Therefore, this research focus on the benefits of the recycling method for handling construction waste in the construction sector. This study aims to promote the benefits of the recycling methods for construction waste. It focused on interviewing 2 contractor companies in Kuching, Sarawak for the selected case studies located at Kuching and Samarahan Divisions. In this study, the objectives include determining the potential benefits of recycling methods for construction waste, identifying the best practices of recycling method and recognise the success factors of the recycling method for construction waste. Major findings in this research are regarding the benefits of the recycling method for construction waste. The benefits are including money-saving, time-saving, reduce pollution, less manpower and waste minimization. These benefits are related to the recycling practices being used by the contractor. The outcome of this research highlight that conducting suitable practices of recycling method for construction waste can generate various benefits.